2002
DOI: 10.1093/cercor/12.4.376
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Pain and Somatic Sensation in the Human Insula: a Study of Responses to Direct Electrical Cortical Stimulation

Abstract: We studied painful and non-painful somaesthetic sensations elicited by direct electrical stimulations of the insular cortex performed in 43 patients with drug refractory temporal lobe epilepsy, using stereotactically implanted depth electrodes. Painful sensations were evoked in the upper posterior part of the insular cortex in 14 patients, mostly in the right hemisphere. Non-painful sensations were elicited in the posterior part of the insular cortex in 16 patients, in both hemispheres. Thus, painful and non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
278
0
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 499 publications
(319 citation statements)
references
References 83 publications
32
278
0
9
Order By: Relevance
“…A similar lack of electrophysiological data is also the case for the adjacent dorsal insula. Direct stimulation of the insula in humans has elicited painful responses [Ostrowsky et al, 2002], and lesions incorporating S2 and adjacent insula have fundamental effects on the quality of pain sensations evoked by contralateral peripheral stimulation [Greenspan et al, 1999]. The results of the meta-analysis provide further impetus for investigations that will refine our understanding of the role of this region in pain processing.…”
Section: Discussionmentioning
confidence: 97%
“…A similar lack of electrophysiological data is also the case for the adjacent dorsal insula. Direct stimulation of the insula in humans has elicited painful responses [Ostrowsky et al, 2002], and lesions incorporating S2 and adjacent insula have fundamental effects on the quality of pain sensations evoked by contralateral peripheral stimulation [Greenspan et al, 1999]. The results of the meta-analysis provide further impetus for investigations that will refine our understanding of the role of this region in pain processing.…”
Section: Discussionmentioning
confidence: 97%
“…A lesion of the ascending lamina I fibres in the middle of the lateral funiculus, a lesion of the VMpo or a lesion of dorsal posterior insula (dpIns) can cause the complete and permanent loss of pain and temperature sensation in a contralateral region of the body [5][6][7][8] . Conversely, micro stimulation in either the VMpo or the dpIns in awake humans can cause a well localized report of either sensation 9,10 . The existence of this pathway has generated debate (for example, see , but there is no comparable evidence in rodents -rodents do not have either of these forebrain structures.…”
mentioning
confidence: 99%
“…In one of these, the over-activation of both areas was reported in patients with anxiety disorder [219], while in another study the ventral agranular frontoinsula was shown to co-activate with the amygdala in social-emotional paradigms [38,45,52,228].…”
Section: Insular Cortex and Amygdala Interactionsmentioning
confidence: 99%
“…Such studies include anatomical, electrophysiological, lesion, pharmacological and imaging studies, as well as operatory stimulation techniques which have yielded plausible roles for the IC in dozens of different functions. Several studies indicate that the IC is involved in taste processing [7,8,28,41], viscerosensory information processing [3,20,26,38,42,43], temperature and pain perception [44,45], olfaction [46] auditory processing [47][48][49], somatosensory perception [49,50], drug craving [51], motor tasks [52] and post-stroke motor-recovery functions [53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation